Solos carbonáticos e interações pedogeomorfológicas no semiárido baiano: da evolução da paisagem ao processo de desertificação. - Marcio Lima Rios (2021)
In the Salitre River basin, in the state of Bahia, the interactions between semiarid climate and soils with calcic and calcretic horizons impose peculiar natural conditions in the composition of the landscape. This study proposes to relate materials and processes, mainly involving calcification in soils, dynamics, and evolution of slopes and desertification, analyzed from interrelated elements at different spatial scales. The objective is to understand the evolutionary dynamics and attributes of carbonate and their interaction with actual morphodynamics, aiming to investigate a possible process of desertification in progress. The research was carried out from a multiscale spatial investigation, using different techniques. At the macroscale, information was systematized on the environmental context of the middle course of the Salitre River basin and the interpretation of satellite images, aerial photographs, relief morphometry, and Monte Carlo simulation for soil loss in the area. At the mesoscale, the analyzes focused on the slope, with a morphological description of soil profiles in toposequence, quantitative studies related to linear erosion, and identification of natural and anthropogenic features. At the microscale, we used soil micromorphology techniques. An area of 80 km2 was delimited corresponding to a relief compartment called valley bottom depression (dfv), which, in a more general view, presents large whitish spatial spots, which predominantly represent powdery calcretes, calcrete saprolites, and subsurface calcic horizons (colluvial materials) exposed, which were pickled by erosive action. In the toposequence, the few spots with solum mainly constitute carbonates HAPLIC CAMBISOLS, supported by materials with high contents of Equivalent Calcium Carbonate (500 g kg-1, up to 900 g kg-1), representing one of the areas with higher content of secondary carbonates in soils in Brazil. Typical features of CaCO3 precipitation in the soil were found, such as calcitic coatings and hypocoatings, calcitic fillings and individualized and coalesced carbonate nodules, associated with the first phases of the formation of a pedogenic calcrete profile, consistent with the current conditions of the local semiarid climate. On the slopes, in interaction with the materials mentioned above, 145,526 m of linear erosive features were mapped in a 20.8 km2 section, constituting aggressive mechanisms for soil removal and resulting debris from the Salitre River drainage. In the evolution of the local relief, there is a close relationship between quaternary climatic oscillations and local morphodynamics, pointing to the notching of the drainage in wetter periods than today, the slope retreat with the valley's pleasantness in the semiarid periods and climatic transitions. Currently, the landscape experiences a morphodynamics of retreat of slopes with intense deterioration of carbonate soils and with chemical limitations due to the regeneration of vegetation, interacting with high levels of poverty, and a human occupation substantially based on the suppression of vegetation cover, responsible for the expansion of soil exposure in recent decades (from 31% in 1950 to 69% in 2019). This unstable environmental context coincides with what has been called extreme degradation of arid and semiarid lands, an essential condition for installing a desertification process.